Legible religion: books, gods, and rituals in Roman culture - MacRae, Duncan (Harvard University Press, 2016)
"What was the significance of books in a religion without a sacred text? From the beginning of critical study of religion, the presence of Scripture - sacred and authoritative texts - has divided a few privileged Religions of the Book from other religions, including Roman religion, that lack such books. Arguing that we should look beyond this distinction, Legible Religion examines the role of books in Roman religious culture. In order to get at the question of the place of books in religion, the study includes an extended comparison between Roman books on their religion and the Mishnah, an early Rabbinic compilation of Jewish practice and law, to highlight how non-Scriptural texts can play an important part in the demarcation of religious systems."--Provided by publisher